Sodium hydrosulfide modifies the nutrient ratios of soybean (Glycine max) under iron deficiency. Issue 2 (7th February 2018) - Chen, Juan; Shang, Yu-Ting; Zhang, Ni-Na; Zhong, Yangquanwei; Wang, Wen-Hua; Zhang, Jian-Hua; Shangguan, Zhouping
Abstract: Iron (Fe) deficiency in calcareous soils is a major limiting factor which influences production and yield of field crops. The present study investigated the effect of NaHS, a donor of H2 S, which is emerging as a potential signaling molecule, on the nutrient ratios of soybean ( Glycine max L.) under Fe deficiency. Soybean seedlings with and without NaHS were subjected to Fe deficiency and Fe sufficiency for 18 d. Subsequently, we determined the biomass of seedlings, chlorophyll concentration, Fe concentration, as well as the ratios of carbon (C), nitrogen (N), phosphorus (P), and potassium (K). The growth of soybean seedlings was inhibited by Fe deficiency. However, under Fe deficiency the application of NaHS increased the biomass as well as the Fe, N, P, and K concentrations compared to the controls. Furthermore, our results also show that the application of NaHS affected the ratios of C : N, C : P, C : K, N : P, N : K, and P : K in soybean seedlings under Fe deficiency and sufficiency. H2 S played an important role in promoting the growth of soybean seedlings by enhancing the accumulation of nutrients under Fe deficiency.